Confirmatory factor analysis towards visionary leadership of supply chain managers in the manufacturing industry of Thailand - Bunnoiko, Kasem; Atthirawong, Walailak (My University, 2017)
Visionary leadership is defined as one's ability to clearly perceive and foresee the future in order to prepare to face the unpredictable consequences. Hence, the aim of this paper is to examine factors affecting visionary leadership of logistics and supply chain managers. Five factors, namely, creativity, communication, organisation climate, emotional intelligence and traits were identified from relevant researches. This study explored with supply chain managers in the anufacturing industry of Thailand with 560 samples of 4636 total population. The confirmatory factor analysis (CFA) was tested with second order. It was revealed that the model fit confirms as appropriate (GFI = 0.953, AGFI = 0.930, CFI = 0.986 and RMSEA = 0.042). It showed that the model is valid and reliable to the visionary leadership for supply chain managers in the manufacturing industry of Thailand. On the basis of these current data it appears that five factors influence their visionary leadership.
Keywords: Communication; Creativity; Emotional intelligence; Manufacturing; Organisational climate; Supply chain management; Traits; Visionary leadership